Chloride Penetration Profile of Polyvinyl Alcohol (PVA) Treated Oil Palm Shell (OPS) Concrete - Thong, C. C.; Teo, DCL; Ng, CK (2015)
Oil palm shell (OPS) is the hard endocarp which surrounds the palm kernel and received as crushed pieces during the extraction of palm oil. It is an agricultural waste and can be found in abundance in Malaysia. Economic and environmental benefits as well as decreasing the use of natural resources can be achieved if OPS can be utilised as a building material. Promising results showed that OPS has good potential to be used as coarse aggregate replacement in making structural lightweight concrete. It has also been previously established that polyvinyl alcohol (PVA) can be used to improve the properties of OPS concrete. Chloride induced reinforcement corrosion is an important area of study which needs to be investigated, especially for concrete structures exposed to marine environments. Therefore, this paper presents an experimental study on the chloride penetrability of PVA treated OPS concrete in comparison to that of raw OPS concrete using the 90-day salt ponding test. The effects of different curing conditions (full water curing, air-dry curing and site curing) on the chloride penetration resistance of PVA treated OPS concrete and raw OPS concrete were also studied. Both PVA treated OPS and raw OPS concrete surface were ponded with 3% sodium chloride solution up to 90 days, and the chloride profiles were measured by analysing concrete dust samples extracted from different depth intervals from the chloride exposed concrete surface. Subsequently, chloride diffusion coefficients were determined by fitting the experimental data to Fick’s second law of diffusion. From the test results, it was found that PVA treated OPS concrete had high surface chloride concentration as compared to raw OPS concrete. However, PVA treated OPS concrete showed higher resistance to chloride penetration as compared to raw OPS concrete as indicated from the chloride diffusion coefficient. The results indicated that curing conditions also have a significant influence on the chloride resistance of PVA treated OPS concrete and raw OPS concrete.